2003
DOI: 10.1089/154099903321154130
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Orientation and Variation in Physical and Mental Health Status among Women

Abstract: In this rare opportunity to use population-based data to study lesbian and bisexual health, we found that sexual orientation as a nonheterosexual woman was associated with increased rates of poor physical and mental health. We believe these findings support the need for the increased systematic study of the relationship between sexual orientation and health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
0
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(93 citation statements)
references
References 24 publications
3
84
0
5
Order By: Relevance
“…Similar to other studies that used convenience-based sampling from the visible lesbian community (Bradford and Ryan, 1988;Cochran et al, 2001;Fifield et al, 1975;Peterson, 1989a, 1989b;Roberts and Sorensen, 1999;Skinner, 1994;Skinner and Otis, 1996) or systematic health surveys of women in the general (Bloomfield, 1993;Cochran et al, 2000;Diamant and Wold, 2003;Diamant et al, 2000;Gruskin et al, 2001;McCabe et al, 2003;Nawyn et al, 2000;Russell et al, 2002;Scheer et al, 2002), we observed that homosexually experienced women interviewed in the CWHS were more likely to report smoking tobacco, drinking alcohol, and using alcohol in a somewhat more dysfunctional manner than exclusively heterosexually experienced women. But at the same time, our findings suggest that both age and patterns of sexual partner gender choice are important factors to consider in understanding the differences in substance use behavior among women who may vary in their same-sex sexual behavior patterns.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Similar to other studies that used convenience-based sampling from the visible lesbian community (Bradford and Ryan, 1988;Cochran et al, 2001;Fifield et al, 1975;Peterson, 1989a, 1989b;Roberts and Sorensen, 1999;Skinner, 1994;Skinner and Otis, 1996) or systematic health surveys of women in the general (Bloomfield, 1993;Cochran et al, 2000;Diamant and Wold, 2003;Diamant et al, 2000;Gruskin et al, 2001;McCabe et al, 2003;Nawyn et al, 2000;Russell et al, 2002;Scheer et al, 2002), we observed that homosexually experienced women interviewed in the CWHS were more likely to report smoking tobacco, drinking alcohol, and using alcohol in a somewhat more dysfunctional manner than exclusively heterosexually experienced women. But at the same time, our findings suggest that both age and patterns of sexual partner gender choice are important factors to consider in understanding the differences in substance use behavior among women who may vary in their same-sex sexual behavior patterns.…”
Section: Discussionmentioning
confidence: 84%
“…Accumulating evidence suggests that lesbians and bisexual women may represent a subpopulation at especially elevated risk for the harmful health effects from alcohol and tobacco use (Bradford et al, 1994;Cochran, 2001;Cochran et al, 2000;Diamant et al, 2000;Fifield et al, 1975;Gruskin et al, 2001;Hughes and Eliason, 2002;Israelstam and Lambert, 1983;Peterson, 1989a, 1989b;Nardi, 1982;Roberts and Sorensen, 1999;Skinner, 1994;Skinner and Otis, 1996). Although findings observed across surveys of lesbians and bisexual women have not been entirely consistent (Bloomfield, 1993;Cochran et al, 2003;Roberts and Sorensen, 1999), typically women classified as lesbian or bisexual, as compared to heterosexual women, more commonly report being a current or former tobacco smoker (Bradford and Ryan, 1988;Cochran et al, 2001;Diamant and Wold, 2003;Diamant et al, 2000;Gruskin et al, 2001), appear less likely to abstain from alcohol consumption (Cochran et al, 2000;Diamant et al, 2000;Roberts and Sorensen, 1999), evidence a pattern of alcohol use that includes more frequent consumption as well as greater amounts drunk, though typically still within a moderate range (Diamant et al, 2000;Hughes and Eliason, 2002;Roberts and Sorensen, 1999), and perhaps fail to show normative age-related declines in alcohol use (Abbott, 1998;Bradford et al, 1994;Gruskin et al, 2001;Hughes and Wilsnack, 1997;Peterson, 1989a, 1989b). Although only a minority of lesbians and bisexual women in these surveys evidence problematic drinking behavior, the prevalences observed are generally higher than those reported by heterosexual women.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,8 However, in studies that have examined bisexual people separately, they report poorer mental health and higher rates of mental health service utilization than do heterosexuals 1,[9][10][11][12][13][14] and, in some studies, than do lesbians and gay men. [10][11][12][13][14] Various factors have been proposed to explain the association of bisexuality with these poor mental health outcomes, including the relative invisibility of bisexual people and a resulting lack of in-group community support.…”
mentioning
confidence: 99%
“…Bisexuals may be at a higher risk than heterosexual individuals and, in some cases, at a higher risk than gay and lesbians for health and mental health problems, higher rates of mental health service utilization, substance use, as well as suicidality (e.g., Bostwick & Hequembourg, 2014;Case et al, 2004;Diamant & Wold, 2003;Jorm, Korten, Rodgers, Jacomb, & Christensen, 2002;Kerr, Santurri, & Peters, 2013;Ross et al, 2010;Sarno & Wright, 2013;Tjepkema, 2008). Meyer (1995) posits that such disparities are often attributed to stressors related to minority status, including experiences of prejudice and discrimination.…”
Section: Background and Significancementioning
confidence: 99%